Wide temperature enhanced sodium storage in tailored, sustainable sodiophilic biphasic N-doped carbon - Yadav, Poonam; Das, Anoushka K.; Torris, Arun; Wasnik, Kundan; Koppisetti, Heramba Venkata Sai Rama Murthy; Pol, Vilas G.; Shelke, Vilas; Shelke, Manjusha (Materials Today Chemistry, 2024)
Alternative to Li-ion batteries(LIB), Na-ion batteries (NIB) and Na metal batteries (NMB) are gaining significant attention due to their low cost, abundance, and safety. By modulating microstructural properties such as graphitization, heteroatom doping, surface-rich functional groups, and interlayer d-spacing, Na-ion storage in NIB and Na plating/striping in NMB can be ameliorated. This study reports sodiophilic N-doped polymer-derived carbon (PDC) as an anode for NIB and host for Na metal in NMB. As NIB anode, PDC provides a storage capacity of 173 mAh g- 1 at 1 A g- 1 in half-cell and 84 mAh g- 1 at 1C (1C = 128 mAhg- 1) in full-cell with Na3V2(PO4)2F3 (NVPF) cathode. As Na metal anode (NMA) host, a high columbic efficiency (C.E.) of 99.45% for over 1000 cycles at 6 mA cm- 2_4 mAh cm-2 is obtained. Furthermore, fascinating wide temperature (50 degrees C and -20 degrees C) sodiumion storage is successfully demonstrated by PDC. Advanced X-ray photoelectron spectroscopy (XPS) confirmed the formation of stable and uniform solid electrolyte interphase (SEI) composed of inorganic and organic components, X-ray microtomography confirmed uniform Na plating throughout the volume of the electrode analogous to Brunauer-Emmett-Teller (BET) surface area, Raman spectroscopy, X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) results. A sustainable and scalable promising biphasic NIB anode and sodiophilic host for Na metal was possible due to larger d-spacing, partial graphitization, high mesoporosity, N-doping, presence of surface functional groups, better charge transfer, and diffusion properties.
Keywords: Full-cell; Low and elevated temperatures; Na metal host; Polymer-derived carbon; Sodium-ion battery; X-ray tomography